PERAN RASIO KEUANGAN DALAM MENGUKUR KINERJA DAN STABILITAS KEUANGAN PT ANEKA GAS INDUSTRI TBK - Triani Triani; Nurdhiana Nurdhiana; Indah Budi Sulistyowati (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to determine the financial ratio analysis of liquidity, profitability, and solvency at PT. Aneka Gas Industri Tbk. on 2018-2021 period. In this study using comparative causal research. Based on the type of data studied, this research is included in the type of archival research. Archival research is research on written facts (documents) or in the form of data archives. The data used are annual financial reports and annual reports of  PT. Aneka Gas Industri in 2018-2021. Based on the research results prove that the current ratio, debt to equity ratio, debt to asset ratio at PT. Aneka Gas Industri on 2018-2021 period is good, while the quick ratio, return on assets, return on equity at PT. Aneka Gas Industri on 2018-2021period are not good.